Profiling the satisfaction of tourists visiting Mabul Island as a tourist destination based on demographic factors - Caroline Geetha B. Arokiadasan; Rosle Mohidin; Tini Maizura Mohtar; Azaze@Azizi Hj. Abdul Adis (Global Academic Excellence, 2022)
The study aims to examine whether the satisfaction of the tourists in visiting Mabul Island as a tourist destination can be influence by demographic variables. The study involves primary data collection where questionnaire was used as the instrument to collect information. The questionnaire was distributed both physically in the island and also through Google Form. The questionnaire was distributed to 169 respondents selected through nonprobability sampling, purposive sampling method. The questionnaire was divided into 2 sections. The first section enquires information on the demography of the respondents. Section 2 measures the satisfaction of the tourists. The satisfaction was measured using 5 dimensions. The information was analysed using descriptive and inferential statistics. The result revealed that the profiling the satisfaction of tourists in choosing Mabul Island as a tourist destination were insignificant based on the demographic variables.